Correction of Cosmetic Problems to a Previous Hair Transplantation with Overly low Hairline Case - Lin, Yi Jung; Tzou, Chi Chen (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
The most common unconvinced result secondary to hairline transplant include unreasonable low hairline, unnatural hair flow, poor follicle survival rate, unsightly appearance of plugs, blunted temporal angle, large hairless gap posterior to the low hairline, and lack of consideration for progressive hair loss of younger patients with a family history of androgenetic alopecia. Androgenic alopecia often starts from bilateral frontotemporal recession. The patients who come to the hair clinic for hair transplantation always request doctors to focus on the hairline restoration. However, they often demand an extremely low hairline due to their unrealistic comparison with their natural facial proportion. A low hairline may result in the disproportionality of the face, especially compared with peers of the same age, additional hair loss behind the planted new hairline, inadequate hairs in the backside of the head (donor site), and so on. Facing the patients who come for the hairline correction, a professional hair doctor should try to explain the progress of the hair loss, recommending them to fine-tune an appropriate height to preserve the follicle reservoir for the need in future. A practical approach to managing these cosmetic problems secondary to a previous hairline transplant will be presented in the article.